A method for preparing glass fiber reinforced polypropylene composite material

Through the modified glass fiber surface treatment and the use of silicon oxygen modified color masterbatch, the connection strength and masterbatch stability of glass fiber reinforced polypropylene composite materials are solved, the mechanical properties and color effects of the material are improved, and the more Good polypropylene bonds with glass fiber and masterbing stability.

CN117209812BActive Publication Date: 2025-01-14LONGZHIYAO (ZHEJIANG) NEW MATERIAL TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310964184.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-08-02
Publication Date
2025-01-14
Estimated Expiration
2043-08-02

AI Technical Summary

Technical Problem

The connection strength of the existing glass fiber reinforced polypropylene composite materials is poor, which leads to the easy fall off and powdering of glass fibers, and the color influence range of the masterbing material becomes smaller and the connectivity decreases during use.

Method used

By modifying the surface treatment of the glass fiber, a silicon-titanium-oxygen composite shell is formed to improve the mechanical properties and stability of the glass fiber. Silicon-oxygen modified color masterbatch is used to improve the stability and connectivity of the color masterbatch, combined with Malay Acid anhydride grafting polypropylene as a compatibilizer to enhance the connectivity between polypropylene and glass fibers.

Benefits of technology

It improves the tensile properties and structural stability of glass fibers, enhances the mechanical properties of composite materials, ensures the long-term stability and color effect of color masterbing, and improves the binding performance of polypropylene and glass fibers.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004372836310000101
    Figure BDA0004372836310000101
  • Figure BDA0004372836310000111
    Figure BDA0004372836310000111
Patent Text Reader

Abstract

The present invention belongs to the field of polypropylene composite materials, and specifically relates to a preparation method of a glass fiber reinforced polypropylene composite material, wherein the mass ratio of the composite material is: 40-50 parts of polypropylene resin, 40-50 parts of modified glass fiber, 4-6 parts of compatibilizer, and 4-6 parts of modified masterbatch, and a specific preparation method is provided. The present invention solves the problem that the existing glass fiber reinforced polypropylene has poor connection strength, and utilizes the surface modification of glass fiber and the compatibilizer to improve the connectivity between polypropylene and glass fiber. At the same time, the stretchability of the glass fiber itself is improved by the modification method, and the structural stability of the long fiber is ensured.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of polypropylene composite materials, and in particular relates to a preparation method of a glass fiber reinforced polypropylene composite material. Background Art

[0002] Polypropylene resin is a general thermoplastic with excellent comprehensive performance. It has many advantages: rich raw material sources, simple production process, low price, high commercial value; medium tensile strength and flexural strength, easy to fill and modify, and the mechanical properties are greatly improved after modification; high heat resistance temperature, can be used at temperatures above 100°C; excellent fatigue resistance under repeated bending loads; excellent electrical insulation performance, and is not affected by humidity; good chemical resistance; almost insoluble in any solvent at room temperature, and is not affected by the corrosion of inorganic salt aqueous solutions, inorganic acids and inorganic alkalis. Therefore, polypropylene materials have good applications in many fields.

[0003] Glass fiber reinforced polypropylene composite material is a thermoplastic polymer-based composite material with glass fiber as a reinforcing agent. It is known as the green and environmentally friendly material of the 21st century. In the automotive industry, it is widely used to manufacture bumpers, rear luggage racks, seats, fenders, wheel covers and other parts. Since the interaction between glass fiber and polymer matrix is ​​very weak, it is easy to fall off from the polymer matrix to form voids. Summary of the invention

[0004] In view of the problems in the prior art, the present invention provides a method for preparing a glass fiber reinforced polypropylene composite material, which solves the problem that the existing glass fiber reinforced polypropylene has poor connection strength. The surface modification of the glass fiber is combined with a compatibilizer to improve the connectivity between the polypropylene and the glass fiber. At the same time, the tensile properties of the glass fiber itself are improved by modification to ensure the structural stability of the long fiber.

[0005] In order to achieve the above technical objectives, the technical solution of the present invention is:

[0006] A method for preparing a glass fiber reinforced polypropylene composite material, wherein the mass ratio of the composite material comprises:

[0007] 40-50 parts of polypropylene resin, 40-50 parts of modified glass fiber, 4-6 parts of compatibilizer, and 4-6 parts of modified masterbatch.

[0008] The polypropylene resin is one of Y2600, Y1600, BX3800 and BH3800.

[0009] The modified glass fiber adopts silicon-titanium modified long glass fiber; the length of the silicon-titanium modified long glass fiber is 0.6-1.2mm; the surface of the glass fiber contains a large number of pits and cracks, resulting in uneven distribution of its surface activity. Therefore, the connection force of the polypropylene resin on the surface of the glass fiber is unevenly distributed, and interface gaps are very likely to appear, thereby causing the glass fiber to fall off and powder. The silicon-titanium modified long glass fiber forms a shell structure on the surface of the long glass fiber, and the shell structure can wrap the long glass fiber. The activity of the silicon-oxygen structure and the titanium-oxygen structure itself can be effectively improved. At the same time, the structural stability of the silicon-oxygen structure and the titanium-oxygen structure itself can effectively improve the long glass fiber. The mechanical properties of the glass fiber, combined with the permeability of the silicon-oxygen structure and the titanium-oxygen structure, fill most of the dents and cracks, thereby achieving an improvement in the mechanical properties and ensuring the stability of the long glass fiber; the preparation method of the silicon-titanium modified long glass fiber comprises: a1, isothermal ablation of the long glass fiber for 20 minutes, ultrasonically cleaning it in an alkaline solution for 20 minutes after cooling, ultrasonically cleaning it with distilled water after taking it out and drying it to obtain an active glass fiber; the temperature of the isothermal ablation is 250°C, the alkaline solution is a sodium hydroxide solution with a pH of 10, the ultrasonic frequency of the ultrasonic cleaning is 60kHz, and the temperature is 50°C; the ultrasonic frequency of the ultrasonic cleaning is 80kHz, and the temperature is 10℃; this step uses a constant temperature ablation method to completely sinter the organic impurities on the surface of the long glass fiber, improve the surface cleanliness, and reduce the coverage of the long glass fiber by organic impurities; the surface of the long glass fiber is activated by the erosion of sodium hydroxide by an alkaline solution. At the same time, the inorganic impurities adsorbed on the surface of the long glass fiber are separated when the surface of the glass fiber is corroded, and the high-frequency vibration of the ultrasound is combined to achieve the bare effect; a2, silicon tetrachloride is added to anhydrous ether and stirred evenly to form a silicon-based filling liquid, and then the active glass fiber is placed and ultrasonically treated for 30 minutes, and then taken out and kept at a constant temperature for 1 hour to obtain the repaired glass fiber; the concentration of the silicon tetrachloride in anhydrous ether is 100g / L, the stirring speed for uniform stirring is 500r / min, the concentration of the active glass fiber in the silicon-based filling liquid is 40g / L, the ultrasonic frequency of the ultrasonic treatment is 60kHz, and the temperature is 5°C; the temperature of the constant temperature static is 40°C, the static atmosphere is a mixed atmosphere of nitrogen and water vapor, and the water vapor in the mixed atmosphere accounts for 6%; this step utilizes the solubility of silicon tetrachloride in ether to form a homogenized dispersed structure, and uses ultrasonic immersion to put the glass fiber into the dissolving liquid. Silicon tetrachloride forms a stable deposition based on the activity of the glass fiber surface, and the active groups between the pits and microcracks are relatively aggregated, which can form a good deposition adsorption;During the constant temperature standing process, the ether gradually volatilizes, and the silicon tetrachloride is gradually precipitated to form a liquid film filling, and cooperates with the water molecules in the air to form an in-situ hydrolysis system, which is converted into a tetrahydroxy structure, thereby promoting the connection and filling of the silicon tetrachloride material and the glass fiber. Based on the fact that the main component of the glass fiber is silicon dioxide, it belongs to a homogeneous filling system with silicon tetrahydroxy; a3, silicon tetrachloride, ethyl titanate and ethyl cellulose are added to the ether for ultrasonic dispersion for 30 minutes to obtain a mixed solution; then the glass fiber is placed in the mixed solution for immersion and pulling treatment, and is dried at a constant temperature to obtain a coated glass fiber, wherein the molar ratio of silicon tetrachloride to ethyl titanate is 3:1, the amount of ethyl cellulose added is 10% of the molar amount of silicon tetrachloride, the concentration of silicon tetrachloride in the ether is 100g / L, the ultrasonic frequency of the ultrasonic dispersion is 70kHz, and the temperature is 5°C; the immersion speed of the immersion and pulling treatment is 6cm / min, and the pulling speed is 3cm / min, the constant temperature drying temperature is 40°C, this step utilizes the solubility of ethyl cellulose, silicon tetrachloride and ethyl cellulose in ether to achieve a homogeneous dispersion effect of the three in ether, and then the dissolved liquid is hung on the specific surface of the glass fiber during the dipping and pulling process to achieve a liquid film hanging effect, and the coated glass fiber is obtained by constant temperature drying; at the same time, in this process, ethyl cellulose itself has a certain viscosity, and a viscous liquid is formed in the ether to ensure that it forms a stable hanging coating effect on the surface of the glass fiber; a4, the coated glass fiber is allowed to stand in the reactor for 2h, and after nitrogen purging, constant temperature light treatment is performed for 5h to obtain silicon-titanium modified glass fiber, the standing atmosphere is a mixed atmosphere of nitrogen and water vapor, and the volume proportion of water vapor in the mixed atmosphere is 10%, the nitrogen purging temperature is 40°C, the purging speed is 155mL / min, and the constant temperature light treatment uses sunlight at a temperature of 230°C;When the coated glass fiber is left standing in the reactor, silicon tetrachloride and ethyl titanate in the surface film react with water molecules in situ to form titanic acid and silicic acid, while ethyl cellulose as a spacer does not dissolve, and the reaction impurities and excess water vapor generated are removed during the purging process. During the constant temperature light treatment process, titanic acid and silicic acid form a condensation reaction to obtain a composite mesoporous structure, and titanic acid is converted into anatase titanium dioxide, which degrades ethyl cellulose under light conditions. At the same time, sunlight irradiation can promote the degradation of ethyl cellulose, that is, during the light treatment process, ethyl cellulose is not only subjected to light degradation treatment, but also subjected to photocatalytic degradation of silica. At this time, the silica shell does not form a light shielding, ensuring that the light penetrates inward. The modified glass fiber prepared by this process forms a silicon-titanium composite shell on the surface of the glass fiber. The shell is rich in a large number of hydroxyl structures, and there are microporous structures and mesoporous structures in the shell, which increases the content of active groups on the surface of the glass fiber and effectively improves the mechanical properties of the glass fiber. At the same time, the microporous structure and mesoporous structure can promote the penetration of polypropylene in the molten state to form a physical staggered structure, which improves the bonding performance of the glass fiber and polypropylene. At the same time, the structural system can ensure that the glass fiber maintains a complete long fiber structure and is not easy to break. ;

[0010] The compatibilizer is maleic anhydride grafted polypropylene.

[0011] The modified masterbatch adopts a silicone-modified masterbatch, which has a masterbatch material as the core and a silicone material as the shell; the masterbatch adopts one of carbon black, titanium oxide, and phthalocyanine blue. The masterbatch has the effect of changing color and coloring the polypropylene composite material. However, in actual use, the masterbatch material is completely wrapped by the polypropylene resin, resulting in a smaller range of color influence. At the same time, based on the chemical inertness of polypropylene itself, the connectivity between the masterbatch and the polypropylene resin decreases, and powdering is very likely to occur. The preparation method of the modified masterbatch comprises the following steps; b1, grinding the masterbatch particles in ether for 20 minutes, and drying by nitrogen purge to obtain a fine powder masterbatch; the mass ratio of the masterbatch to ether is 3:1, the grinding pressure of the grinding treatment is 0.3-0.4MPa, and the temperature is 5°C; the temperature of the nitrogen purge is 60°C, and the speed is 40mL / min; this step uses ether as a solvent to wet-grind the masterbatch particles to form a homogeneous masterbatch powder, and uses a nitrogen purge system of a constant temperature system to convert the ether into b2, adding trichloromethylsilane to ether and ultrasonically dispersing for 50 minutes to obtain a silane solution, and then adding the masterbatch powder to the silane solution and ultrasonically mixing for 60 minutes to obtain a suspension; the concentration of the trichloromethylsilane in ether is 200g / L, the ultrasonic frequency of the ultrasonic dispersion is 80kHz, and the temperature is 10°C; the concentration of the masterbatch powder in the silane solution is 80g / L, the ultrasonic frequency of the ultrasonic mixing is 90kHz, and the temperature is 5°C; this step is to use Using the solubility of trichloromethylsilane in ether, ultrasonic dispersion is used to form a solution of trichloromethylsilane, and then the masterbatch powder is added to the solution, and the trichloromethylsilane is evenly dispersed on the surface of the masterbatch powder by ultrasonic mixing, and the bubbles on the surface of the masterbatch powder are removed to improve the adhesion of the trichloromethylsilane on the surface of the masterbatch powder; b3, spraying the suspension into a reactor and letting it stand to obtain a modified masterbatch powder; the spraying speed of the suspension is 20 mL / min, the spraying area is 200 cm2, and the atmosphere of the reactor is The mixture is a mixed atmosphere of nitrogen and water vapor, and the volume ratio of nitrogen to water vapor is 8:1. The temperature in the reactor is 60°C, and the static temperature is 100°C. The temperature setting is used to ensure that ether evaporates to form gas, and trichloromethylsilane is converted into liquid and wrapped on the surface of the masterbatch powder to form a homogeneous wrapping structure. In the process, trichloromethylsilane encounters water molecules to form in-situ hydrolysis, and the in-situ hydrolysis is evenly wrapped on the surface of the masterbatch powder to form hydroxyl polycondensation under temperature conditions to obtain a siloxane-modified masterbatch.The modified masterbatch prepared by this process contains a silica shell layer on its surface, which has good transparency and stability, and has excellent stability for the masterbatch itself, thereby improving the stability and long-term effectiveness of the masterbatch. At the same time, the silica shell layer can utilize its own hydroxyl activity to improve its connectivity with the modified glass fiber and the compatibilizer, thereby improving its stability in the entire system. Secondly, the silica-modified masterbatch contains a mesoporous silica structure, which can promote the penetration of the resin in the molten state and achieve a physical fixation effect.

[0012] The preparation method of the glass fiber reinforced polypropylene composite material comprises the following steps:

[0013] Step 1, uniformly stirring the modified glass fiber and the modified masterbatch, then sequentially adding the polypropylene resin and the compatibilizer component to mix, and plasticizing and melting to obtain a molten polypropylene resin solution; the temperature of the plasticizing and melting is 180-220° C.;

[0014] Step 2: Extruding the molten resin into a melt impregnation mold through a twin-screw extruder, and cooling and solidifying it to obtain a glass fiber reinforced polypropylene composite material.

[0015] It can be seen from the above description that the present invention has the following advantages:

[0016] 1. The present invention solves the problem of poor connection strength of existing glass fiber reinforced polypropylene. The surface modification of glass fiber is used in combination with a compatibilizer to improve the connectivity between polypropylene and glass fiber. At the same time, the modification method is used to improve the tensile properties of the glass fiber itself to ensure the structural stability of the long fiber.

[0017] 2. The present invention forms a silicon-oxygen structure on the surface of the masterbatch by means of surface modification, thereby ensuring the long-term stability of the masterbatch, and at the same time utilizing the light transmittance of the silicon-oxygen material to ensure that the modified system has no effect on the light of the masterbatch. DETAILED DESCRIPTION

[0018] The present invention is described in detail with reference to the embodiments, but no limitation is imposed on the claims of the present invention.

[0019] Example 1

[0020] The invention discloses a method for preparing a glass fiber reinforced polypropylene composite material. The composite material consists of polypropylene resin, modified glass fiber, a compatibilizer and a modified masterbatch.

[0021] The polypropylene resin is Y2600.

[0022] The modified glass fiber adopts silicon-titanium modified long glass fiber; the length of the silicon-titanium modified long glass fiber is 0.6mm; the preparation method of the silicon-titanium modified long glass fiber comprises: a1, isothermal ablation of the long glass fiber for 20min, after cooling, ultrasonic cleaning in an alkaline solution for 20min, taking out, ultrasonic cleaning with distilled water and drying to obtain active glass fiber; the temperature of the isothermal ablation is 250°C, the alkaline solution is a sodium hydroxide solution with a pH of 10, the ultrasonic cleaning frequency is 60kHz, and the temperature is 50°C; the ultrasonic cleaning The frequency is 80kHz and the temperature is 10°C; a2, silicon tetrachloride is added to anhydrous ether and stirred evenly to form a silicon-based filling liquid, and then the active glass fiber is placed and ultrasonically treated for 30 minutes, and then taken out and allowed to stand at a constant temperature for 1 hour to obtain the repaired glass fiber; the concentration of the silicon tetrachloride in anhydrous ether is 100g / L, the stirring speed for uniform stirring is 500r / min, the concentration of the active glass fiber in the silicon-based filling liquid is 40g / L, the ultrasonic frequency of the ultrasonic treatment is 60kHz, and the temperature is 5°C; the temperature of the constant temperature standing is 40°C , the static atmosphere is a mixed atmosphere of nitrogen and water vapor, and the water vapor in the mixed atmosphere accounts for 6%; a3, silicon tetrachloride, ethyl titanate and ethyl cellulose are added to ether and ultrasonically dispersed for 30 minutes to obtain a mixed solution; then the glass fiber is immersed in the mixed solution and pulled, and dried at a constant temperature to obtain a coated glass fiber, the molar ratio of silicon tetrachloride to ethyl titanate is 3:1, the amount of ethyl cellulose added is 10% of the molar amount of silicon tetrachloride, the concentration of silicon tetrachloride in ether is 100g / L, and the ultrasonic frequency of the ultrasonic dispersion is 70 kHz, the temperature is 5°C; the immersion speed of the immersion and pulling treatment is 6cm / min, the pulling speed is 3cm / min, and the temperature of the constant temperature drying is 40°C; a4, the coated glass fiber is allowed to stand in the reactor for 2h, and after nitrogen purging, it is treated with constant temperature light for 5h to obtain silicon-titanium modified glass fiber, the standing atmosphere is a mixed atmosphere of nitrogen and water vapor, and the volume proportion of water vapor in the mixed atmosphere is 10%, the temperature of the nitrogen purging is 40°C, the purging speed is 155mL / min, and the constant temperature light treatment uses sunlight at a temperature of 230°C.

[0023] The compatibilizer is maleic anhydride grafted polypropylene.

[0024] The modified masterbatch adopts a silicon-oxygen modified masterbatch, which has a masterbatch material as a core and a silicon-oxygen material as a shell; the masterbatch adopts carbon black, and the preparation method of the modified masterbatch comprises the following steps: b1, grinding the masterbatch particles in ether for 20 minutes, and drying by nitrogen purge to obtain a fine powder masterbatch; the mass ratio of the masterbatch to ether is 3:1, the grinding pressure of the grinding process is 0.3-0.4MPa, and the temperature is 5°C; the temperature of the nitrogen purge is 60°C, and the speed is 40mL / min; b2, adding trichloromethylsilane to the ether and ultrasonically dispersing for 50 minutes to obtain a silane solution, and then adding the masterbatch powder to the silane solution for ultrasonic mixing 60min to obtain a suspension; the concentration of trichloromethylsilane in ether is 200g / L, the ultrasonic frequency of ultrasonic dispersion is 80kHz, and the temperature is 10°C; the concentration of the masterbatch powder in the silane solution is 80g / L, the ultrasonic frequency of ultrasonic mixing is 90kHz, and the temperature is 5°C; b3, spraying the suspension into a reactor and letting it stand to obtain a modified masterbatch powder; the spraying speed of the suspension is 20mL / min, the spraying area is 200cm2, the atmosphere of the reactor is a mixed atmosphere of nitrogen and water vapor, and the volume ratio of nitrogen to water vapor is 8:1, the temperature in the reactor is 60°C, and the standing temperature is 100°C.

[0025] The preparation method of the glass fiber reinforced polypropylene composite material comprises the following steps:

[0026] Step 1, weighing raw materials according to the mass ratio of 40 parts of polypropylene resin, 40 parts of modified glass fiber, 4 parts of compatibilizer, and 4 parts of modified masterbatch;

[0027] Step 2, uniformly stirring the modified glass fiber and the modified masterbatch, then sequentially adding the polypropylene resin and the compatibilizer component to mix, and plasticizing and melting to obtain a molten polypropylene resin solution; the temperature of the plasticizing and melting is 180° C.;

[0028] Step 3, extruding the molten resin melt into a melt impregnation mold through a twin-screw extruder, and cooling and solidifying it to obtain a glass fiber reinforced polypropylene composite material.

[0029] Example 2

[0030] The invention discloses a method for preparing a glass fiber reinforced polypropylene composite material. The composite material consists of polypropylene resin, modified glass fiber, a compatibilizer and a modified masterbatch.

[0031] The polypropylene resin is Y1600.

[0032] The modified glass fiber adopts silicon-titanium modified long glass fiber; the length of the silicon-titanium modified long glass fiber is 1.2 mm; the preparation method of the silicon-titanium modified long glass fiber comprises: a1, isothermal ablation of the long glass fiber for 20 minutes, after cooling, ultrasonic cleaning in an alkaline solution for 20 minutes, taking out, ultrasonic cleaning with distilled water and drying to obtain active glass fiber; the temperature of the isothermal ablation is 250°C, the alkaline solution is a sodium hydroxide solution with a pH of 10, the ultrasonic cleaning frequency is 60kHz, and the temperature is 50°C; the ultrasonic cleaning The frequency is 80kHz and the temperature is 10°C; a2, silicon tetrachloride is added to anhydrous ether and stirred evenly to form a silicon-based filling liquid, and then the active glass fiber is placed and ultrasonically treated for 30 minutes, and then taken out and allowed to stand at a constant temperature for 1 hour to obtain the repaired glass fiber; the concentration of the silicon tetrachloride in anhydrous ether is 100g / L, the stirring speed for uniform stirring is 500r / min, the concentration of the active glass fiber in the silicon-based filling liquid is 40g / L, the ultrasonic frequency of the ultrasonic treatment is 60kHz, and the temperature is 5°C; the temperature of the constant temperature standing is 40°C , the static atmosphere is a mixed atmosphere of nitrogen and water vapor, and the water vapor in the mixed atmosphere accounts for 6%; a3, silicon tetrachloride, ethyl titanate and ethyl cellulose are added to ether and ultrasonically dispersed for 30 minutes to obtain a mixed solution; then the glass fiber is immersed in the mixed solution and pulled, and dried at a constant temperature to obtain a coated glass fiber, the molar ratio of silicon tetrachloride to ethyl titanate is 3:1, the amount of ethyl cellulose added is 10% of the molar amount of silicon tetrachloride, the concentration of silicon tetrachloride in ether is 100g / L, and the ultrasonic frequency of the ultrasonic dispersion is 70 kHz, the temperature is 5°C; the immersion speed of the immersion and pulling treatment is 6cm / min, the pulling speed is 3cm / min, and the temperature of the constant temperature drying is 40°C; a4, the coated glass fiber is allowed to stand in the reactor for 2h, and after nitrogen purging, it is treated with constant temperature light for 5h to obtain silicon-titanium modified glass fiber, the standing atmosphere is a mixed atmosphere of nitrogen and water vapor, and the volume proportion of water vapor in the mixed atmosphere is 10%, the temperature of the nitrogen purging is 40°C, the purging speed is 155mL / min, and the constant temperature light treatment uses sunlight at a temperature of 230°C.

[0033] The compatibilizer is maleic anhydride grafted polypropylene.

[0034] The modified masterbatch adopts a silicon-oxygen modified masterbatch, which has a masterbatch material as a core and a silicon-oxygen material as a shell; the masterbatch adopts titanium oxide, and the preparation method of the modified masterbatch comprises the following steps: b1, grinding the masterbatch particles in ether for 20 minutes, and drying by nitrogen purging to obtain a fine powder masterbatch; the mass ratio of the masterbatch to ether is 3:1, the grinding pressure of the grinding treatment is 0.3-0.4MPa, and the temperature is 5°C; the temperature of the nitrogen purging is 60°C, and the speed is 40mL / min; b2, adding trichloromethylsilane to the ether and ultrasonically dispersing for 50 minutes to obtain a silane solution, and then adding the masterbatch powder to the silane solution for ultrasonic mixing; b3, spraying the suspension into a reactor and letting it stand to obtain a modified masterbatch powder; the spraying speed of the suspension is 20 mL / min, the spraying area is 200 cm2, the atmosphere of the reactor is a mixed atmosphere of nitrogen and water vapor, and the volume ratio of nitrogen to water vapor is 8:1, the temperature in the reactor is 60 ° C, and the standing temperature is 100 ° C.

[0035] The preparation method of the glass fiber reinforced polypropylene composite material comprises the following steps:

[0036] Step 1, weighing raw materials according to the mass ratio of 50 parts of polypropylene resin, 50 parts of modified glass fiber, 6 parts of compatibilizer, and 6 parts of modified masterbatch;

[0037] Step 2, uniformly stirring the modified glass fiber and the modified masterbatch, then sequentially adding the polypropylene resin and the compatibilizer component to mix, and plasticizing and melting to obtain a molten polypropylene resin solution; the temperature of the plasticizing and melting is 220° C.;

[0038] Step 3, extruding the molten resin melt into a melt impregnation mold through a twin-screw extruder, and cooling and solidifying it to obtain a glass fiber reinforced polypropylene composite material.

[0039] Example 3

[0040] The invention discloses a method for preparing a glass fiber reinforced polypropylene composite material. The composite material consists of polypropylene resin, modified glass fiber, a compatibilizer and a modified masterbatch.

[0041] The polypropylene resin is BX3800.

[0042] The modified glass fiber adopts silicon-titanium modified long glass fiber; the length of the silicon-titanium modified long glass fiber is 1.0 mm; the preparation method of the silicon-titanium modified long glass fiber comprises: a1, isothermal ablation of the long glass fiber for 20 minutes, after cooling, ultrasonic cleaning in an alkaline solution for 20 minutes, taking out, ultrasonic cleaning with distilled water and drying to obtain active glass fiber; the temperature of the isothermal ablation is 250°C, the alkaline solution is a sodium hydroxide solution with a pH of 10, the ultrasonic cleaning frequency is 60kHz, and the temperature is 50°C; the ultrasonic cleaning The frequency is 80kHz and the temperature is 10°C; a2, silicon tetrachloride is added to anhydrous ether and stirred evenly to form a silicon-based filling liquid, and then the active glass fiber is placed and ultrasonically treated for 30 minutes, and then taken out and allowed to stand at a constant temperature for 1 hour to obtain the repaired glass fiber; the concentration of the silicon tetrachloride in anhydrous ether is 100g / L, the stirring speed for uniform stirring is 500r / min, the concentration of the active glass fiber in the silicon-based filling liquid is 40g / L, the ultrasonic frequency of the ultrasonic treatment is 60kHz, and the temperature is 5°C; the temperature of the constant temperature standing is 40°C , the static atmosphere is a mixed atmosphere of nitrogen and water vapor, and the water vapor in the mixed atmosphere accounts for 6%; a3, silicon tetrachloride, ethyl titanate and ethyl cellulose are added to ether and ultrasonically dispersed for 30 minutes to obtain a mixed solution; then the glass fiber is immersed in the mixed solution and pulled, and dried at a constant temperature to obtain a coated glass fiber, the molar ratio of silicon tetrachloride to ethyl titanate is 3:1, the amount of ethyl cellulose added is 10% of the molar amount of silicon tetrachloride, the concentration of silicon tetrachloride in ether is 100g / L, and the ultrasonic frequency of the ultrasonic dispersion is 70 kHz, the temperature is 5°C; the immersion speed of the immersion and pulling treatment is 6cm / min, the pulling speed is 3cm / min, and the temperature of the constant temperature drying is 40°C; a4, the coated glass fiber is allowed to stand in the reactor for 2h, and after nitrogen purging, it is treated with constant temperature light for 5h to obtain silicon-titanium modified glass fiber, the standing atmosphere is a mixed atmosphere of nitrogen and water vapor, and the volume proportion of water vapor in the mixed atmosphere is 10%, the temperature of the nitrogen purging is 40°C, the purging speed is 155mL / min, and the constant temperature light treatment uses sunlight at a temperature of 230°C.

[0043] The compatibilizer is maleic anhydride grafted polypropylene.

[0044] The modified masterbatch adopts a silicon-oxygen modified masterbatch, which has a masterbatch material as a core and a silicon-oxygen material as a shell; the masterbatch adopts phthalocyanine blue, and the preparation method of the modified masterbatch comprises the following steps: b1, grinding the masterbatch particles in ether for 20 minutes, and drying by nitrogen purge to obtain a fine powder masterbatch; the mass ratio of the masterbatch to ether is 3:1, the grinding pressure of the grinding treatment is 0.3-0.4MPa, and the temperature is 5°C; the temperature of the nitrogen purge is 60°C, and the speed is 40mL / min; b2, adding trichloromethylsilane to the ether and ultrasonically dispersing for 50 minutes to obtain a silane solution, and then adding the masterbatch powder to the silane solution for ultrasonic mixing; b3, spraying the suspension into a reactor and letting it stand to obtain a modified masterbatch powder; the spraying speed of the suspension is 20 mL / min, the spraying area is 200 cm2, the atmosphere of the reactor is a mixed atmosphere of nitrogen and water vapor, and the volume ratio of nitrogen to water vapor is 8:1, the temperature in the reactor is 60 ° C, and the standing temperature is 100 ° C.

[0045] The preparation method of the glass fiber reinforced polypropylene composite material comprises the following steps:

[0046] Step 1, weighing raw materials according to the mass ratio of 45 parts of polypropylene resin, 45 parts of modified glass fiber, 6 parts of compatibilizer, and 4 parts of modified masterbatch;

[0047] Step 2, uniformly stirring the modified glass fiber and the modified masterbatch, then sequentially adding the polypropylene resin and the compatibilizer component to mix, and plasticizing and melting to obtain a molten polypropylene resin solution; the temperature of the plasticizing and melting is 200° C.;

[0048] Step 3, extruding the molten resin melt into a melt impregnation mold through a twin-screw extruder, and cooling and solidifying it to obtain a glass fiber reinforced polypropylene composite material.

[0049] Comparative Example 1

[0050] The invention discloses a method for preparing a glass fiber reinforced polypropylene composite material. The composite material consists of polypropylene resin, modified glass fiber, a compatibilizer and a modified masterbatch.

[0051] The polypropylene resin is BX3800.

[0052] The length of the glass fiber is 1.0 mm.

[0053] The compatibilizer is maleic anhydride grafted polypropylene.

[0054] The color masterbatch is phthalocyanine blue.

[0055] The preparation method of the glass fiber reinforced polypropylene composite material comprises the following steps:

[0056] Step 1, weighing raw materials according to the mass ratio of 45 parts of polypropylene resin, 45 parts of glass fiber, 6 parts of compatibilizer, and 4 parts of masterbatch;

[0057] Step 2, uniformly stirring the modified glass fiber and the modified masterbatch, then sequentially adding the polypropylene resin and the compatibilizer component to mix, and plasticizing and melting to obtain a molten polypropylene resin solution; the temperature of the plasticizing and melting is 200° C.;

[0058] Step 3, extruding the molten resin melt into a melt impregnation mold through a twin-screw extruder, and cooling and solidifying it to obtain a glass fiber reinforced polypropylene composite material.

[0059] Comparative Example 2 uses pure polypropylene resin

[0060] Performance Testing

[0061]

[0062]

[0063] The above data show that the glass fiber reinforced polypropylene composite material of the present technical solution has enhanced tensile strength and reduced elongation at break compared with ordinary glass fiber polypropylene composite materials, showing good mechanical properties. At the same time, after testing, the products of Examples 1-3 all have good wear resistance, and no obvious change was found after being stored at 150°C for 700 hours. The present technical solution adopts glass fiber as filler to achieve lightweight composite materials, and at the same time, uses glass fiber modification to effectively improve the composite effect, thereby achieving excellent performance of the composite material.

[0064] It is understood that the above specific description of the present invention is only used to illustrate the present invention and is not limited to the technical solutions described in the embodiments of the present invention. Those skilled in the art should understand that the present invention can still be modified or replaced by equivalents to achieve the same technical effects; as long as the use requirements are met, they are within the protection scope of the present invention.

Claims

1. A method for preparing a glass fiber reinforced polypropylene composite material, characterized in that: The mass ratio of the composite material includes: 40-50 parts of polypropylene resin, 40-50 parts of modified glass fiber, 4-6 parts of compatibilizer, 4-6 parts of modified masterbatch; The modified glass fiber adopts silicon-titanium modified long glass fiber; and the surface of the silicon-titanium modified long glass fiber has a microporous structure and a mesoporous structure; the length of the silicon-titanium modified long glass fiber is 0.6-1.2mm; the preparation method of the silicon-titanium modified long glass fiber comprises: a1, isothermal ablation of the long glass fiber for 20min, after cooling, ultrasonic cleaning in an alkaline solution for 20min, taking out, ultrasonic cleaning with distilled water and drying to obtain an active glass fiber; the temperature of the isothermal ablation is 250°C, the alkaline solution is a sodium hydroxide solution with a pH of 10, and the ultrasonic frequency of the ultrasonic cleaning is The ultrasonic frequency of the ultrasonic washing is 80kHz and the temperature is 10℃; a2, silicon tetrachloride is added to anhydrous ether and stirred evenly to form a silicon-based filling liquid, and then the active glass fiber is placed and ultrasonically treated for 30 minutes, and then taken out and allowed to stand at a constant temperature for 1 hour to obtain the repaired glass fiber; the concentration of silicon tetrachloride in anhydrous ether is 100g / L, the stirring speed for uniform stirring is 500r / min, the concentration of the active glass fiber in the silicon-based filling liquid is 40g / L, the ultrasonic frequency of the ultrasonic treatment is 60kHz, and the temperature is 5 ℃; the temperature of the constant temperature static state is 40℃, the static state atmosphere is a mixed atmosphere of nitrogen and water vapor, and the volume proportion of water vapor in the mixed atmosphere is 6%; a3, silicon tetrachloride, ethyl titanate and ethyl cellulose are added to ether and ultrasonically dispersed for 30 minutes to obtain a mixed solution; then the glass fiber is immersed in the mixed solution and pulled, and the coated glass fiber is dried at a constant temperature, the molar ratio of silicon tetrachloride to ethyl titanate is 3:1, the amount of ethyl cellulose added is 10% of the molar amount of silicon tetrachloride, the concentration of silicon tetrachloride in ether is 100g / L, and the ultrasonic dispersion The ultrasonic frequency is 70kHz and the temperature is 5°C; the immersion speed of the immersion and pulling treatment is 6cm / min, the pulling speed is 3cm / min, and the temperature of the constant temperature drying is 40°C; a4, the coated glass fiber is allowed to stand in the reactor for 2h, and after nitrogen purging, it is treated with constant temperature light for 5h to obtain silicon-titanium modified glass fiber, the standing atmosphere is a mixed atmosphere of nitrogen and water vapor, and the volume proportion of water vapor in the mixed atmosphere is 10%, the temperature of the nitrogen purging is 40°C, the purging speed is 155mL / min, and the constant temperature light treatment uses sunlight at a temperature of 230°C.

2. The method for preparing a glass fiber reinforced polypropylene composite material according to claim 1, characterized in that: The polypropylene resin is one of Y2600, Y1600, BX3800 and BH3800.

3. The method for preparing the glass fiber reinforced polypropylene composite material according to claim 1, characterized in that: The compatibilizer is maleic anhydride grafted polypropylene.

4. The method for preparing a glass fiber reinforced polypropylene composite material according to claim 1, characterized in that: The modified masterbatch is a silicon-oxygen modified masterbatch.

5. The method for preparing a glass fiber reinforced polypropylene composite material according to claim 4, characterized in that: The silicon-oxygen modified masterbatch has a masterbatch material as a core and a silicon-oxygen material as a shell.

6. The method for preparing a glass fiber reinforced polypropylene composite material according to claim 4, characterized in that: The color masterbatch is one of carbon black, titanium oxide and phthalocyanine blue.

7. The method for preparing a glass fiber reinforced polypropylene composite material according to claim 1, characterized in that: The preparation method of the glass fiber reinforced polypropylene composite material comprises the following steps: Step 1, uniformly stirring the modified glass fiber and the modified masterbatch, then sequentially adding the polypropylene resin and the compatibilizer component to mix, and plasticizing and melting to obtain a molten polypropylene resin melt; the temperature of the plasticizing and melting is 180-220° C.; Step 2: Extruding the molten resin into a melt impregnation mold through a twin-screw extruder, and cooling and solidifying it to obtain a glass fiber reinforced polypropylene composite material.

Citation Information

Patent Citations

  • Long glass fibre reinforced polypropylene material and preparation method thereof

    CN102010546A

  • High-strength glass fiber composite material and processing technology thereof

    CN109929132A